2022
DOI: 10.15376/biores.17.1.1373-1384
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylated nanocrystalline cellulose from Salix psammophila prepared by sulfuric acid hydrolysis combined with 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidation

Abstract: Salix psammophila (SP) is an important sand plant, and could be utilized to develop high-value products. In this work, SP was used as raw material and cellulose nanocrystals (CNC) were prepared by hydrolysis in 64 wt% sulfuric acid (H2SO4) solution, and then, TEMPO/NaBr/NaClO system was used to oxidize CNC to obtain TEMPO-oxidation-cellulose nanocrystals (TOCNC). Fourier transform infrared analysis (FTIR) revealed that after oxidation, there were obvious carboxyl functional groups. Scanning electron microscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…S1 † shows the infrared spectra of CCF versus untreated virgin cellulose fibers (CF), CCF shows a distinct infrared characteristic peak at 1600 cm −1 compared to CF, which is attributed to the asymmetric contraction vibration of –COO–, indicating successful oxidation of CF. 23 The peak around 3300 cm −1 is attributed to the O–H stretching vibration, this comes from physically adsorbed water. 24 The bands at 490 cm −1 in MOF-199 and MOF-199/CCF are attributed to the Cu–O metal–oxygen bond, and the peaks at 728 cm −1 and 761 cm −1 are attributed to C–H stretching.…”
Section: Resultsmentioning
confidence: 99%
“…S1 † shows the infrared spectra of CCF versus untreated virgin cellulose fibers (CF), CCF shows a distinct infrared characteristic peak at 1600 cm −1 compared to CF, which is attributed to the asymmetric contraction vibration of –COO–, indicating successful oxidation of CF. 23 The peak around 3300 cm −1 is attributed to the O–H stretching vibration, this comes from physically adsorbed water. 24 The bands at 490 cm −1 in MOF-199 and MOF-199/CCF are attributed to the Cu–O metal–oxygen bond, and the peaks at 728 cm −1 and 761 cm −1 are attributed to C–H stretching.…”
Section: Resultsmentioning
confidence: 99%
“…It can be used to determine the size, shape, and distribution of the particles. TEM results from several researchers showed that NCC are needle-like or rod like in shape [42,43].…”
Section: Transmission Electron Microscopy (Tem)mentioning
confidence: 99%
“…As a lignocellulosic biomass, cellulose, hemicellulose, and lignin are the main components of S. psammophila. In recent years, the liquefaction of this plant under sulfuric acid, nitric acid, or hydrochloric acid catalysis have been studied (Zhong et al 2020(Zhong et al , 2022. However, it is well established that the highly hydrogen-bonded cellulose component cannot be easily dissolved in any conventional solvents (Maldas and Shiraishi 1997).…”
Section: Introductionmentioning
confidence: 99%